EVALUASI KEBUTUHAN JARINGAN IRIGASI (STUDI KASUS DAERAH IRIGASI BATANG ANAI) SUB-DI LUBUK ALUNG MENGGUNAKAN PROGRAM CROPWAT 8.0 DAN HEC-RAS 5.0.1 - Afandi, Ahmad; Nofrizal, Nofrizal; Yulan Nifen , Silta; Agus, Agus (Jurnal Teknologi dan Vokasi, 2024)
The Lubuk Alung Irrigation Area is a grouping of the large Batang Anai Irrigation Area, generally most of the population are farmers, so the need for water for agricultural land is very necessary, if there is a lack of water supply for irrigation it can hamper the pace of the planting season. The aim of this research is to calculate the need for irrigation water in rice fields and plantations in the Lubuk Alung irrigation area and determine the exiting dimension. Calculation of irrigation water requirements using the KP-01 method and Cropwat 8.0 software, to find the exiting dimensions using HEC-RAS 5.0.1 software. From the results of calculating irrigation water requirements using the KP-01 method, the value was 1.42 l/sec/ha in April and the results of calculating irrigation water requirements using the Cropwat 8.0 program obtained a value of 0.36 l/sec/ha in March. . In the cross section calculation using HEC-RAS 5.0.1 software, the discharge used is in the primary channel BLS.1-BLS.2, namely 21,566 m3//s with data on the dimensions of the upstream channel (P0) with channel width (b) = 11 m , channel height H = 2.87 m and downstream channel height (P16) (H) = 3.14 m, from the results of running with HEC-RAS 5.0.1 software it is found that the water level upstream is (P0) (h) = 1.2 m and the water level downstream (P16) (h) = 1.13 m, while from field survey data it was found that the water level upstream (P0) (h) = 1.23 m and downstream (P16) (h) = 1.15 m. From the results seen in the cross section image, it can be concluded that the channel dimensions are not the same height. In overcoming this problem, an attempt was made to recreate an efficient channel cross-section design. The results obtained from exiting channel dimensions with channel bottom width (b) = 8 m, channel top width (B) = 17.76 m, water level height (h) = 1.56 m, channel height (H) = 2.44 m , and guard height (w) = 0.88 m.